Multi-effect nursing toothpaste with cream texture and preparation method thereof
By using a specific ratio of toothpaste components and the super-micro-crosslinked polyquaternium-22, the balance between antibacterial properties and stability in toothpaste is solved, achieving high stability and multi-effect care for cream-textured toothpaste, including rapid sterilization, long-lasting antibacterial effect, enamel repair, and anti-sensitivity.
Patent Information
- Application Number
- CN202410020942.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-05
- Publication Date
- 2026-01-13
AI Technical Summary
Existing toothpastes struggle to balance antibacterial properties and stability, and lack effective repair functions for cavities and tooth sensitivity.
Using a specific ratio of phase A, phase B, and phase C components, including super micro-crosslinked polyquaternium-22, thickeners, and functional inorganic salts, a micro-crosslinked spatial system is formed to enhance the stability of the toothpaste and the long-lasting antibacterial effect of the antibacterial agent. The hydrophobic groups of the polyquaternium salt form a flexible network structure, which, combined with thickeners such as hydroxyethyl cellulose, achieves enamel repair and anti-sensitivity effects.
This toothpaste achieves a creamy texture with high stability and flexibility, while also possessing multiple benefits such as rapid sterilization, long-lasting antibacterial effect, enamel repair, and relief of tooth sensitivity, significantly improving the overall performance of the toothpaste.
Smart Images

Figure BDA0004652680360000051 
Figure BDA0004652680360000061 
Figure BDA0004652680360000062
Abstract
Description
Technical Field
[0001] This invention belongs to the field of cosmetics, particularly to the field of A61K8 / 03, and more specifically to a multi-effect care toothpaste with a creamy texture and its preparation method. Background Technology
[0002] White teeth and a fresh breath can significantly enhance one's image and confidence, and more and more people are realizing the importance of dental health. Oral inflammation, such as periodontitis and dental caries, is one of the most common factors affecting oral health in modern society. Dental caries, also known as cavities, is a progressive lesion of the hard tissues of the teeth, mainly involving the demineralization of inorganic matter and the decomposition of organic matter. The medical community believes that the occurrence of dental caries requires the simultaneous presence of three factors: bacteria, diet, and host. Time is also a factor influencing the development of dental caries. If dental caries is left untreated or unrepaired, it can lead to tooth loss, loose teeth, decreased chewing function, and pulpitis. While prescription drugs are used clinically to treat oral inflammation and are fast-acting, they can cause bacteria to develop drug resistance. Therefore, various protective toothpastes have emerged on the market, incorporating antibacterial components to provide some antibacterial properties. However, these products may offer both long-lasting and rapid antibacterial effects, or long-lasting antibacterial effects but the introduction of antibacterial agents may degrade the stability of the toothpaste. In addition to antibacterial and breath-freshening properties, repairing tooth enamel, stopping bleeding, and soothing are also product functions that consumers demand.
[0003] Existing technology CN109512739A discloses a Tibetan medicine adult toothpaste, in which the Tibetan medicine powder contains Terminalia chebula, senna leaves, and cloves. However, Terminalia chebula has thick cell walls, and direct grinding and pulverization cannot efficiently extract the effective components inside, greatly reducing its antibacterial and anti-inflammatory effects. Existing technology patent CN100562307C discloses an antibacterial toothpaste and its manufacturing method. Its raw materials include bactericides, humectants, anionic surfactants, binders, foaming agents, abrasives, etc., which have antibacterial properties and can inhibit common pathogenic bacteria in the oral cavity and have a certain degree of stability. However, it does not solve the problem of demonstrating anti-sensitivity, soothing, and enamel-repairing functions. Summary of the Invention
[0004] To address the aforementioned technical problems, the first aspect of this invention provides a multi-effect toothpaste with a creamy texture, the raw materials of which include: phase A, phase B, and phase C, with a mass ratio of (20-50):(30-50):(0.0001-1); phase A includes water and a humectant; phase B includes a thickener, a foaming agent, a flavoring agent, an antibacterial agent, a sweetener, an antioxidant, an abrasive, and a functional inorganic salt; the thickener includes a polyquaternium salt with a molecular weight greater than 1,000,000; the functional inorganic salt includes at least sodium monofluorophosphate; and phase C includes a colorant.
[0005] Preferably, the moisturizer comprises one or more of the following: glycerin, bisabolol, 1,4-butanediol, xylitol, sorbitol, 1,3-propanediol, pentanediol, and 1,2-hexanediol.
[0006] More preferably, the moisturizer includes glycerin and sorbitol.
[0007] More preferably, the mass ratio of glycerol, sorbitol and water is (5-10):(10-20):(30-50).
[0008] Preferably, the molecular weight of the polyquaternary ammonium salt is 5,000,000-20,000,000.
[0009] More preferably, the polyquaternium salt comprises polyquaternium salt-22.
[0010] More preferably, the polyquaternium-22 includes one or more of micro-crosslinked polyquaternium-22 or super-micro-crosslinked polyquaternium-22.
[0011] Preferably, the thickener further includes one or more of the following: hydroxyethyl cellulose, cellulose gum, xanthan gum, squalane, polysorbate-60, sodium polyacrylamide dimethyl taurate, and sodium alginate.
[0012] Preferably, the foaming agent comprises one or more of sodium lauryl sulfate, sodium N-lauroyl sarcosinate, cocamidopropyl betaine, and sodium methyl cocoyl taurate.
[0013] More preferably, the foaming agent includes: sodium lauryl sulfate and sodium methyl cocoyl taurate.
[0014] More preferably, the sodium lauryl sulfate and sodium methyl cocoyl taurate are in a ratio of (5-10):(1-10).
[0015] Preferably, the friction agent comprises one or more of the following: silicon dioxide, calcium carbonate, hydrated silica, strontium chloride hexahydrate, dicalcium phosphate, and hydrated alumina.
[0016] More preferably, the friction agent comprises hydrated silica and strontium chloride hexahydrate.
[0017] Preferably, the antioxidants include: benzyl alcohol and ethylhexylglycerin.
[0018] This invention does not specifically limit the fragrance agent; any substance that can enhance the flavor of toothpaste is acceptable, including but not limited to peppermint flavoring.
[0019] This invention does not specifically limit the sweeteners; any substance that can sweeten toothpaste and improve its taste is acceptable, including but not limited to sucralose.
[0020] Preferably, the functional inorganic salt also includes one or more of dipotassium glycyrrhizate and potassium chloride.
[0021] Preferably, component B further includes a pH adjuster. This invention does not specifically limit the pH adjuster; any substance that can adjust the pH of the toothpaste is acceptable, including but not limited to sodium citrate.
[0022] Preferably, the antibacterial agent includes one or more of vitamin B5, allantoin, and polylysine.
[0023] More preferably, the mass ratio of vitamin B5, allantoin, and polylysine is (1-5):(10-20):(15-20).
[0024] This invention does not impose any specific limitations on colorants. Any substance that can sweeten toothpaste and improve its color effect is acceptable, including but not limited to CI77891, CI 77492, CI 77491, CI 77499, CI 74160, CI 77269, and CI42090.
[0025] A second aspect of the present invention provides a multi-effect toothpaste with a creamy texture, comprising at least the following steps:
[0026] S1. Weigh the A-phase material, mix it evenly, and set it aside.
[0027] S2. Weigh in the B phase material and stir until homogeneous;
[0028] S3. Pour phase B into phase A and turn on vacuum stirring.
[0029] S4. Add phase C and continue vacuum stirring to obtain the final product. Attached Figure Description
[0030] Figure 1 This is a 500x SEM image of the control group in an in vitro tooth desensitization efficacy test.
[0031] Figure 2 This is a 500x SEM image of the experimental group used in the in vitro tooth desensitization efficacy test.
[0032] Figure 3 This is a 2000x SEM image of the control group in an in vitro tooth desensitization efficacy test.
[0033] Figure 4 The image shows a 2000x SEM image of the in vitro tooth desensitization efficacy test group.
[0034] Figure 5 This is a 4000x SEM image of the control group in an in vitro tooth desensitization efficacy test.
[0035] Figure 6 This is a 4000x SEM image of the experimental group used in the in vitro tooth desensitization efficacy test.
[0036] Beneficial effects
[0037] (I) The multi-effect care toothpaste provided by this invention has the appearance and stability of a cream texture. The inventors have found that this can only be achieved by strictly controlling the moisturizing components and the ratio of the components to water. In this invention, phase A includes a moisturizer and water, wherein the moisturizer is glycerin and sorbitol. When the mass ratio of glycerin, sorbitol and water is (5-10):(10-20):(30-50) and it is compounded with a specific thickener, the toothpaste has a cream texture and high stability. On the market, toothpastes with similar performance usually contain about 40% glycerin in the raw materials, so the cream texture is poor.
[0038] (II) In this invention, polyquaternium-22 was selected, especially super-micro-crosslinked polyquaternium-22 with a molecular weight of 5,000,000-20,000,000. This effectively regulates the viscosity of the system and enhances its stability. Its ultra-high molecular weight micro-crosslinked spatial network structure can suspend abrasives, colorants, etc., within the system, while simultaneously preventing the possibility of raw material agglomeration. Commonly used abrasives and colorants have a large specific surface area, and due to electrostatic effects, their surfaces carry a large number of negative charges. Super-micro-crosslinked polyquaternium-22 in toothpaste has covalent bond blocking and charge blocking effects. The main chain carries both positive and negative charges, and the positively charged groups can autonomously adsorb onto the surface of solid raw materials, enhancing the suspension ability of solid raw materials. It can also rapidly construct the toothpaste skeleton structure, giving the toothpaste appropriate consistency, good strip formation, strong adhesion to the toothbrush, and preventing collapse or thinning.
[0039] (III) The super-micro-crosslinked polyquaternary ammonium salt used in this invention has hydrophobic groups with long side chains. A large number of these hydrophobic groups aggregate through van der Waals forces, generating association and forming associated regions. These associated regions are relatively soft, enhancing the flexibility of the toothpaste system. Even under extreme conditions such as high temperature (50°C), low temperature (5°C), and freezing (-25°C), the toothpaste system maintains its flexibility, significantly improving the stability of the toothpaste and preserving its creamy texture.
[0040] (iv) The present invention also includes thickeners such as hydroxyethyl cellulose, cellulose gum, and xanthan gum, which can work together with super micro-crosslinked polyquaternary ammonium salt-22 to make the antibacterial agent stable for a long time without losing its activity. Due to its certain viscosity, after brushing teeth with this toothpaste, the antibacterial agent and functional inorganic salt can stay on the tooth surface and oral mucosa for a long time, so that it can not only quickly sterilize, but also achieve a 12-hour long-lasting antibacterial effect.
[0041] (v) The multi-effect care toothpaste with cream texture described in this invention can not only achieve rapid sterilization and long-lasting antibacterial effects, but also repair tooth enamel, improve gum bleeding, and relieve tooth sensitivity. Compared with similar products on the market, it has more effects and a higher cost performance. Detailed Implementation
[0042] Example 1
[0043] The first aspect of this invention provides a multi-effect care toothpaste with a creamy texture, the raw materials of which include phase A, phase B, and phase C, with a mass ratio of 37.57:0.2.
[0044] The A phase, by mass parts, consists of: 6 parts glycerol, 14 parts sorbitol, and 42.23 parts purified water.
[0045] The B phase, by mass parts, comprises: 25 parts hydrated silica, 0.5 parts hydroxyethyl cellulose, 0.8 parts cellulose gum, 1.2 parts super-micro-crosslinked polyquaternium-22, 1 part xanthan gum, 0.03 parts polylysine, 0.5 parts benzyl alcohol, 0.2 parts ethylhexylglycerin, 0.15 parts vitamin B5, 0.15 parts sodium citrate, 1.5 parts potassium chloride, 0.15 parts dipotassium glycyrrhizate, 0.15 parts allantoin, 1.5 parts strontium hexahydrate, 0.24 parts sodium monofluorophosphate, 0.2 parts sucralose, 1.3 parts peppermint flavor, 1.6 parts sodium methyl cocoyl taurate, and 1.4 parts sodium lauryl sulfate.
[0046] The C phase, measured in parts by mass, is 0.2 parts CI77891.
[0047] The super micro-crosslinked polyquaternary ammonium salt-22 mentioned above was purchased from Shenzhen Tai New Material Technology Development Co., Ltd., model number SMPQ-22, with a molecular weight of 5,000,000-20,000,000; the remaining products were all commercially available products.
[0048] The second aspect of this embodiment provides a method for preparing a multi-effect care toothpaste with a creamy texture, specifically comprising the following steps:
[0049] S1. Weigh the A-phase material, mix it evenly, and set it aside.
[0050] S2. Weigh in the B phase material and stir until homogeneous;
[0051] S3. Pour phase B into phase A and turn on vacuum stirring for 30 minutes;
[0052] S4. Add phase C and continue vacuum stirring to obtain the final product.
[0053] Comparative Example 1
[0054] The specific implementation method of this comparative example is the same as that of Example 1, except that the raw materials used in the preparation do not include super-micro-crosslinked polyquaternary ammonium salt-22.
[0055] Comparative Example 2
[0056] The specific implementation method of this comparative example is the same as that of Example 1, except that the raw materials used in the preparation do not include cellulose gum.
[0057] Comparative Example 3
[0058] The specific implementation method of this comparative example is the same as that of Example 1, except that the mass fraction of sorbitol in the raw materials is 10 parts.
[0059] Performance Evaluation
[0060] I. Rapid antibacterial properties
[0061] Test subject: Example 1
[0062] Test method: The test was commissioned to a third-party testing organization, Guangdong Provincial Microbiology Analysis and Testing Center, and the testing standard was QB / T 2738-2012(7.3).
[0063] The test item was rapid antibacterial activity over 1 minute; the test results are detailed in Table 1.
[0064] Table 1
[0065]
[0066]
[0067] Evaluation criteria: When the inhibition rate is ≥90%, the sample has a strong inhibitory effect on the tested strain; when the inhibition rate is ≥50% to 90%, the sample has an inhibitory effect on the tested strain.
[0068] II. Long-lasting antibacterial properties
[0069] Test subject: Example 1
[0070] Test method: The test was commissioned to a third-party testing unit, Shanghai Micro-Spectrum. The test standard was WS / T "Evaluation Method for Antibacterial and Bacteriostatic Effects" 5.1.2 Carrier Immersion Quantitative Antibacterial Experiment, temperature: 21.0℃, humidity: 53%RH.
[0071] The test item was long-lasting antibacterial activity. The test substance was exposed for 12 hours, and the test was repeated 3 times. The test results are detailed in Table 2.
[0072] Table 2
[0073]
[0074] Conclusion: After three repeated tests, the sample showed an inhibition rate of ≥90% against Streptococcus mutans after 12 hours of treatment, indicating a strong antibacterial effect, which meets the requirements of 5.1.2.5 of WS / T 650-2019 "Evaluation Method for Antibacterial and Antimicrobial Effects".
[0075] III. Tooth Enamel Repair Efficacy Test
[0076] Test Object Example 1
[0077] 1. Test Overview
[0078] Acid-etched enamel specimens were subjected to a 37°C cyclic immersion treatment with toothpaste paste and artificial saliva, with deionized water used as a control for simultaneous treatment (simulating 28 days of cycling). The hardness of the enamel specimens before and after treatment was tested, and the hardness difference ΔHV was calculated. The difference in ΔHV between the sample group and the control group was compared to evaluate the toothpaste's repair effect on enamel.
[0079] 2. Equipment and materials
[0080] 2.1 Main equipment: analytical balance, microhardness tester, polishing machine, low-speed precision cutting machine, constant temperature water bath.
[0081] 2.2 Main materials: deionized water, bovine teeth, artificial saliva, citric acid.
[0082] 3. Testing Process
[0083] 3.1 Select caries-free bovine teeth, clean and sterilize them, and then process them into enamel specimens with a size of not less than 5mm*5mm through steps such as cutting, embedding, and polishing.
[0084] 3.2 The original hardness value (HV) of the polished tooth blocks was measured using a microhardness tester. Ten tooth blocks with hardness values between 250HV and 350HV were selected and randomly divided into a sample group and a control group, with five blocks in each group.
[0085] 3.3 A cyclic etching method was adopted, using citric acid solution and artificial saliva to circulate and etch the tooth block.
[0086] 3.4 The hardness value (HV1) of the acid-etched tooth block was measured using a microhardness tester.
[0087] 3.5 A cyclic method was adopted, in which toothpaste paste and artificial saliva were used to simulate cyclic repair of the acid-etched tooth blocks in the sample group for 28 days, while deionized water was used instead of toothpaste paste to perform cyclic treatment on the control group.
[0088] 3.6 The hardness value (HV2) of the tooth block after simulated cyclic repair was measured using a microhardness tester.
[0089] 3.7 Calculate the hardness difference ΔHV before and after the simulated cycle treatment for the sample group and the control group respectively, analyze whether the difference between the two groups is significant, and calculate the enamel strength repair rate (the ratio of the hardness difference before and after treatment in the sample group to the original hardness), the enamel strength enhancement rate (the ratio of the hardness difference before and after treatment in the sample group to the hardness value after acid etching), and the repair ratio (the ratio of the hardness difference before and after treatment in the sample group to the hardness difference before and after treatment in the control group).
[0090] 4. Test Results and Conclusions
[0091] Table 3. Original hardness values (HV) of tooth enamel specimens
[0092]
[0093]
[0094] Table 4. Hardness values (HV) of tooth enamel specimens before cyclic processing.
[0095]
[0096] Table 5 Hardness values (HV) of tooth enamel specimens after cyclic processing
[0097]
[0098] Table 6. Difference in hardness (HV) of tooth enamel specimens before and after simulated cyclic treatment.
[0099]
[0100]
[0101] Table 7 Normality Experiment
[0102] statistics Degrees of freedom Significance result control group 0.962 5 0.823 Normal distribution Sample group 0.888 5 0.348 Normal distribution
[0103] Table 8 Paired Sample Experiment
[0104] T Degrees of freedom Significance result Control group - Sample group -4.246 4 0.013 Significant differences
[0105] Conclusion: Under the experimental conditions, a comparative experiment was conducted on acid-etched enamel specimens using a 28-day cyclic method with toothpaste samples and a control group. The results showed that the average hardness difference before and after treatment in the sample group was greater than that in the control group, and the difference between the two groups was statistically significant. This indicates that the tested toothpaste sample has a repairing effect on damaged tooth enamel. After 28 days of simulated cycling, 6% of the enamel strength was repaired, representing an 18% increase in enamel strength, equivalent to 3.8 times the repair power of the control group.
[0106] IV. In vitro tooth desensitization efficacy test
[0107] Test subject: Example 1, negative control pure water
[0108] Test method: Third-party testing was commissioned to the Guangdong Provincial Center for Microbiology Analysis and Testing. The testing standard was CALT / TM / SOP294, which measures the effectiveness of dentinal tubule sealing in bovine teeth using an in vitro tooth sensitivity model.
[0109] 1. Experimental Materials
[0110] 1.1 Materials: Extracted bovine tooth dentin slices, citric acid, toothbrush, artificial saliva
[0111] 1.2 Instrument: Scanning electron microscope (SEM)
[0112] 2. Experimental Procedure
[0113] 2.1 Preparation of dentin slices:
[0114] Freshly extracted bovine teeth (extraction within one month) were selected, ensuring the crown was intact, without cracks or decay. After thorough cleaning, the teeth were stored in a neutral 10% formaldehyde solution for later use. A low-speed precision cutter was used to cut perpendicular to the long axis of the tooth, obtaining a flat, exposed dentin area with a thickness controlled at 2-3 mm. The dentin sections were polished with silicon carbide sandpaper under water immersion to create a uniform, flat, and smooth surface. The sections were then ultrasonically cleaned three times with pure water, 10 minutes each time. The dentin was then immersed in 10% citric acid for 2 minutes, followed by copious rinsing with pure water and ultrasonic cleaning for 10 minutes. This etching process was repeated three times to obtain dentin sections with open dentinal tubules.
[0115] 2.2 Blocking Experiment: Experimental Treatment
[0116] 2.2.1 The experiment was divided into a control group and a sample group, with 3 replicates in each group.
[0117] Table 9 Experimental Groups and Treatments
[0118] Group Processing conditions control group Wash with pure water and a toothbrush experimental group Test sample + toothbrush cleaning
[0119] 2.2.2 Dentin slides were fixed onto glass slides, with 0.2g of the corresponding test sample placed on each slide. The sample was evenly spread over the entire surface of the slide, moistened with pure water, and brushed for 2 minutes, then left to stand for 2 minutes. The slides were then gently rinsed with pure water for 30 seconds to remove the test sample from the surface. The control group's dentin slides were only brushed with a toothbrush dipped in pure water for 2 minutes, then left to stand for 2 minutes. After processing, the dentin slides were stored in artificial saliva and kept in a 37°C constant temperature water bath. Brushing was performed twice daily for 7 consecutive days.
[0120] 2.3 After drying dentin sections for 6 hours, they were fixed with glutaraldehyde, sputtered with gold, and the occlusion of dentinal tubules was observed under a scanning electron microscope (SEM) at magnifications of 500x, 2000x, and 4000x. Three different regions were randomly selected from each dentin section for observation (magnification of 2000x).
[0121] 2.4 Data Processing: Image-Pro Plus 6.0 was used to automatically calculate the area of the unoccluded dentinal tubules, and then the occlusion rate (PR) of the dentinal tubules in each experimental group was determined. SPSS software was used for statistical analysis, with a significance level of α=0.05.
[0122] Calculation formula: PR=(S2-S1) / S2
[0123] PR: Occlusion rate; S1: Area of open dentinal tubules in the experimental group; S2: Area of open dentinal tubules in the control group.
[0124] 3. Scanning electron microscope (SEM) images
[0125] The control group of the in vitro tooth desensitization efficacy test was visualized using a 500x SEM image. Figure 1 As shown.
[0126] 500x SEM image of the in vitro tooth desensitization efficacy test group as shown below. Figure 2 As shown.
[0127] In vitro tooth desensitization efficacy test control group 2000x SEM image as shown below Figure 3 As shown.
[0128] 2000x SEM image of the in vitro tooth desensitization efficacy test group. Figure 4 As shown.
[0129] In vitro tooth desensitizing efficacy test control group 4000x SEM image as shown below Figure 5 As shown.
[0130] The 4000x SEM image of the in vitro tooth desensitization efficacy test group is shown below. Figure 6 As shown.
[0131] 4. Data Analysis
[0132] Table 10 Dentin tubule occlusion rates in each group
[0133] Group n Unsealed area (μm2) Plugging rate (PR, %) control group 3 279.67±78.50 0.00±0.00 experimental group 3 54.50±30.51 80.51±10.91
[0134] 5. Conclusion
[0135] Scanning electron microscopy (SEM) results showed that in the control group, the dentinal tubules were fully open and clearly morphologically distinct, with only a small amount of visible particulate matter deposits, and the edges between the particulate matter and the dentin surface were clear. In the experimental group, the dentin surface was found to be covered with a large amount of deposits, and most of the dentinal tubules were blocked by particulate deposits that were tightly integrated with the dentin surface and were relatively evenly distributed.
[0136] The dentinal tubule occlusion rate was calculated using image analysis (Table 10). The results showed that the unoccluded area of dentinal tubules in the experimental group was significantly smaller than that in the control group, and this difference was statistically significant (P<0.05). The occlusion rate in the experimental group was 81%.
[0137] In summary, based on the isolated bovine tooth dentin model, after 7 days of treatment with the test sample, the exposed dentin achieved a sealing rate of 81%, and the dentin surface was covered with a large amount of deposits. This indicates that the toothpaste in Example 1 has a significant sealing effect on dentinal tubules and can counteract dentin hypersensitivity.
[0138] V. Stability Testing
[0139] Test subjects: Example 1, Comparative Examples 1-3
[0140] Test method: The toothpaste product is left to stand at room temperature for 7 days. Then, the viscosity, pH and color of the toothpaste are tested and observed to see if there are any obvious changes. If there are no obvious changes, it is considered to have excellent stability; otherwise, it is considered to have poor stability.
[0141] Table 11
[0142] Stability test Example 1 Excellent stability Comparative Example 1 Poor stability Comparative Example 2 Poor stability Comparative Example 3 Poor stability
Claims
1. A multi-effect toothpaste with a creamy texture, characterized in that: The raw materials for preparation include: phase A, phase B, and phase C, with a mass ratio of (20-50):(30-50):(0.0001-1); phase A includes water and a humectant; phase B includes a thickener, a foaming agent, a fragrance, an antibacterial agent, a sweetener, an antioxidant, an abrasive, and a functional inorganic salt; the thickener includes a polyquaternary ammonium salt with a molecular weight greater than 1,000,000; the functional inorganic salt includes at least sodium monofluorophosphate; and phase C includes a colorant.
2. The multi-effect toothpaste with a creamy texture according to claim 1, characterized in that: The molecular weight of the polyquaternary ammonium salt is 5,000,000-20,000,000.
3. The multi-effect toothpaste with a creamy texture according to claim 2, characterized in that: The polyquaternary ammonium salts include polyquaternary ammonium salt-22.
4. The multi-effect toothpaste with a creamy texture according to claim 3, characterized in that: The polyquaternary ammonium salt-22 includes one or more of micro-crosslinked polyquaternary ammonium salt-22 or super-micro-crosslinked polyquaternary ammonium salt-22.
5. The multi-effect toothpaste with a creamy texture according to claim 1, characterized in that: The thickeners also include one or more of hydroxyethyl cellulose, cellulose gum, xanthan gum, squalane, polysorbate-60, sodium polyacrylamide dimethyl taurate, and sodium alginate.
6. The multi-effect toothpaste with a creamy texture according to claim 1, characterized in that: The foaming agent includes one or more of sodium lauryl sulfate, sodium N-lauroyl sarcosinate, cocamidopropyl betaine, and sodium methyl cocoyl taurate.
7. The multi-effect toothpaste with a creamy texture according to claim 1, characterized in that: The antibacterial agent includes one or more of vitamin B5, allantoin, and lysine.
8. The multi-effect toothpaste with a creamy texture according to claim 7, characterized in that: The mass ratio of vitamin B5, allantoin, and lysine is (1-5):(10-20):(15-20).
9. The multi-effect toothpaste with a creamy texture according to claim 1, characterized in that: The functional inorganic salts also include one or more of dipotassium glycyrrhizate and potassium chloride.
10. A method for preparing a multi-effect care toothpaste with a creamy texture according to any one of claims 1-9, characterized in that: At least the following steps are included: S1. Weigh the A phase material, mix it evenly and set it aside; S2. Weigh in the B phase material and stir until homogeneous; S3. Pour phase B into phase A and turn on vacuum stirring; S4. Add phase C and continue vacuum stirring to obtain the final product.
Citation Information
Patent Citations
Antibiotic toothpaste and its making process
CN100562307C
Formula of Tibetan medicine adult toothpaste
CN109512739A